Anaphylactic reactions to biological drugs. Issue 4 (August 2020) - Matucci, Andrea; Vultaggio, Alessandra; Nencini, Francesca; Maggi, Enrico
Abstract : Purpose of review: This review summarizes the current knowledge of the pathogenic mechanisms of biologics-induced anaphylaxis, and the diagnostic and prophylactic strategies in the management of potentially reactive patients, to improve the safety profile of biologics. Recent findings: The recent knowledge on the topic highlights the involvement of both effector and regulatory mechanisms in the immune response to biological agents. In addition, the impact of biological's immunogenicity on hypersensitivity reactions has been confirmed in a wider number of studies, defining some details about the kinetics of antidrug antibodies development, specifically immunoglobulin G (IgG) and immunoglobulin E (IgE). Summary: Biological agents may induce anaphylaxis, mainly through the induction of antidrug antibodies. Biologics-related infusion reactions are often clinically consistent with type I hypersensitivity, but IgG antidrug antibodies may also be involved. The immune response toward biologicals is orchestrated by both effector and regulatory T cells. In addition, nonantibody-dependent mechanisms may occur. Among clinicians persists today again a low awareness, not only of the possibility to understand the immunological mechanisms behind anaphylaxis to biologicals but also the opportunity to apply potential strategies for the management of reactive patients aimed to guarantee a safe retreatment.